A Significant Role of Knowledge Management to Improve the Service Sector Industry - Husain, Munawwer (Prabandhan: Indian Journal of Management, 2012)
This paper deals with various aspects of knowledge management, particularly concentrating on knowledge sharing in the service industry and application of the knowledge management for service sectors. Regarding context of different data sources and the research with qualitative methodology create the in-depth knowledge to understand how to do knowledge work for gaining competitive advantage. Here, emphasis is placed on analysis and evaluation of problems and barriers of both cases as applied from all data collection. The qualitative approach is used to obtain information and analysis of data. The concept of knowledge management was used for the analysis - how we can use the application of knowledge management in the development of the service sector. Problems and barriers of knowledge sharing are also presented in the present paper .The findings show that to improve service and customer satisfaction, the industry has to find out and use knowledge management properly. Knowledge management makes it easy in taking decision and getting the information. The paper focuses only on the section of service industry.